General Ledger Financial Reporting Administration Evaluation in Village-Owned Enterprises: Evaluasi Administrasi Pelaporan Keuangan Buku Besar pada Perusahaan Milik Desa - Akhmad Mulyadi; Syamsudduha Syahrorini (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Village-Owned Enterprises (BUMDes) function as strategic institutions supporting rural economic independence through accountable business management, where reliable financial administration is essential for transparency and decision-making. Specific Background: Within accounting systems, the general ledger serves as the central record of financial transactions prior to the preparation of formal financial statements, making it a critical component of financial reporting administration. Knowledge Gap: Despite its widespread adoption, the implementation of general ledger–based financial reporting systems in BUMDes contexts still presents operational challenges and has not been sufficiently examined through qualitative evaluation at the institutional level. Aims: This study evaluates the general ledger–based financial reporting administration system implemented at BUMDes Arjuna Lestari in Jatiarjo Village, Prigen District, Pasuruan Regency. Results: Using a descriptive qualitative approach with interviews, observation, and documentation studies, the findings indicate that the system supports structured recording of financial transactions and improves traceability of financial data. However, several constraints remain, including limited human resources, continued reliance on manual recording practices, and standard operating procedures that are not yet fully optimized. Novelty: The study provides an in-depth qualitative examination of operational practices and constraints within a village-level financial administration system utilizing a general ledger framework. Implications: The findings suggest the need for capacity development among BUMDes managers, standardized accounting procedures, and the adoption of simple digital financial applications to strengthen the quality and reliability of financial reporting. Highlights: Structured transaction documentation and improved data traceability were observed in organizational accounting practices. Operational constraints include limited managerial capacity, manual bookkeeping practices, and incomplete procedural standards. Strengthening managerial skills and adopting simple digital accounting tools are recommended for better reporting quality. Keywords: BUMDes, Financial Administration System, Financial Reporting, General Ledger, Descriptive Qualitative